Characteristics of Tuberculosis Patients With Drug Resistance at Candi Health Center, Wonoayu Health Center, and Krian Health Center - Candraningtyas, Amanda Tiara; Dony Sulystiono; Siti Maemonah; Suesmini Suprihatin (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Drug-Resistant Tuberculosis (TB) occurs when the M. tuberculosis bacteria become resistant to standard anti-TB drugs. This study aimed to identify the characteristics of patients with drug-resistant TB at Candi, Wonoayu, and Krian Health Centers. The type of research that will be carried out uses qualitative research with a descriptive research design and the research population is all RO TB patients who are undergoing treatment at the Candi Health Center, Wonoayu Health Center, Krian Health Center, totaling 15 people. Data collection uses a questionnaire. The findings revealed that most respondents were of productive age (93.3%), predominantly male (53.3%), with a majority having low BMI (46.6%), junior high school education (53.3%), and being unemployed. It was found that 15 respondents (100%) did not have the habit of consuming alcohol, and most (80%) did not smoke. A significant portion (46.6%) had a history of diabetes mellitus (DM), but none had a history of exposure to other TB patients. The study highlights that factors like productive age, male gender, poor nutrition, and low education levels may increase the risk of drug-resistant TB, while treatment adherence and the absence of smoking and alcohol use are crucial in controlling the disease. This research emphasizes the importance of intervention in the community to increase awareness and prevention of TB RO at the Candi Health Center, Wonoayu Health Center, and Krian Community Health Center.